APLIKASI SISTEM JUAL BELI SEPEDA MOTOR BERBASIS WEB DI USAHA DAGANG (UD) RUHMA MOTOR - ., Sujito; Ruma, Lesa Ahsanti (DINAMIKA DOTCOM, 2012)
Business competition is increasingly fierce to make entrepreneurs find a way to continue to develop and advance their business. Efficiency in the field of administration and finance of particular concern to employers. UD. Ruhma Motors is one company that handles business in buying and selling motorcycles. Currently, efforts UD. Ruhma Motor is developing that require the accuracy of data in the process of buying and selling. This study aims to establish information system selling motorcycles in UD. Ruhma Motor Web-based using php. Methods of research on the development of this information system using the System Development Life Cycle. This research produces information systems web-based trading that can help business owners to continue to monitor the development efforts. Data motors and customers can always controlled and stored neatly in the administrative database that helps officers to make reports. Keywords: systems, information, buying and selling, UD Ruhma Motor